2019
DOI: 10.2196/11109
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Versus Video Assessment of Facial Paralysis: Implications for Telemedicine

Abstract: Background Patients with facial nerve paralysis (FNP) experience challenges in accessing health care that could potentially be overcome by telemedicine. However, the reliability of telemedicine has yet to be established in this field. Objective This study aimed to investigate the consistency between face-to-face and video assessments of patients with FNP by experienced clinicians. Methods A repeated-measures design was used. A total of 7 clin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
20
0
2
Order By: Relevance
“…The significant variation in agreement between the assessments done by video recording vs face to face evaluation may have been attributed to the 2D nature of the video recording. This study suggested that there is promise in utilizing video recordings for the assessment of FNP, but there is need for improvement and further testing using more real time images 27 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The significant variation in agreement between the assessments done by video recording vs face to face evaluation may have been attributed to the 2D nature of the video recording. This study suggested that there is promise in utilizing video recordings for the assessment of FNP, but there is need for improvement and further testing using more real time images 27 …”
Section: Resultsmentioning
confidence: 97%
“…A repeated measures study by Tan et al 27 compared the reliability of telemedicine video evaluation of facial nerve paralysis (FNP) in 28 patients using the House‐Brackmann, Sydney, and Sunnybrook facial grading systems evaluated by 7 clinicians. All three scoring systems demonstrated strong reliability in both mediums, with weak reliability in assessment of synkinesis.…”
Section: Resultsmentioning
confidence: 99%
“…Asynchronous methods for monitoring FNP treatment outcomes have also recently been evaluated by 2 research teams. Tan et al [ 62 ] reported that the assessment of videos using the Sunnybrook and HB scales is as good as a face-to-face assessment, although the lack of real time interaction was judged to limit the value of this approach. Mothes et al [ 63 ] found that automatic Sunnybrook grading of photographs using machine learning can deliver fair agreement compared with the subjective rating of the same photographs.…”
Section: Discussionmentioning
confidence: 99%
“…When the seventh cranial nerve (facial nerve, n. facialis, or NVII) is damaged, a form of facial nerve paralysis (FNP) could occur [ 6 ]. The facial nerve is responsible for the innervation of the mimic muscles, the secretomotor function of several glands (palatine, nasal, salivary, and lacrimal), and the gustatory organ [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is now used in several disciplines in plastic surgery like wound management, burn management, trauma, free-flap care, cleft/palate repair, hand surgery, and maxillofacial. In the field of FNP, there are several forms of telemedicine used, but the results are still varying [ 6 ]. Tan et al mentioned that in the specific field of FNP and telemedicine, there were not a lot of (large) studies conducted and most of the literature is on clinicians who implemented the techniques, without formal studies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%